Fenton-like oxidation of azo dye in aqueous solution using magnetic Fe3O4-MnO2 nanocomposites as catalysts - Fang, Zhen-dong; Zhang, Kai; Liu, Jie; Fan, Jun-yu; Zhao, Zhi-wei (Water Science and Engineering, 2017)
In order to overcome the drawback of the low degree of separation from an aqueous solution of MnO2, Fe3O4-MnO2 core-shell nanocompositeswere used as heterogeneous Fenton-like catalysts for the removal of acid orange 7. On the basis of the catalyst characterization, the catalytic ability of the as-synthesized nanocomposites was examined. The results showed that Fe3O4-MnO2 core-shell nanocomposites had greater catalytic ability than Fe3O4 or MnO2 used alone. Meanwhile, the catalyst dosage, H2O2 dosage, temperature, and initial pH had significant effects on the removal of acid orange 7. A high degree of stability and reusability were exhibited by Fe3O4-MnO2 core-shell nanocomposites.Both HO and HO2 were generated in the reaction and HO was the main radical for the removal of acid orange 7. A mechanism for H2O2 catalytic decomposition using Fe3O4-MnO2 core-shell nanocomposites to produce HO is proposed.? 2017 Hohai University. Production and hosting by Elsevier B.V. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/).